Managing project quality - Kloppenborg, Timothy J., 1953-; Petrick, Joseph A., 1946- (ManagementConcepts, 2002)
Annotation As part of the Project Management Essential Library, this book makes breakthroughs in project quality by combining project management. Guiding you from project initiation through closure, the book provides a detailed stage-specific flowchart of activities correlated with appropriate tools to give you new power to meet customer expectations and institutionalize project quality. A small book that speaks volumes.
Title from title screen.
Keywords: Project management.; Quality assurance.; elektronické knihy; electronic books